2014
DOI: 10.1158/1535-7163.mct-13-0773
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of EZH2 by EPZ-6438 Leads to Potent Antitumor Activity in EZH2-Mutant Non-Hodgkin Lymphoma

Abstract: Mutations within the catalytic domain of the histone methyltransferase EZH2 have been identified in subsets of patients with non-Hodgkin lymphoma (NHL). These genetic alterations are hypothesized to confer an oncogenic dependency on EZH2 enzymatic activity in these cancers. We have previously reported the discovery of EPZ005678 and EPZ-6438, potent and selective S-adenosyl-methionine-competitive small molecule inhibitors of EZH2. Although both compounds are similar with respect to their mechanism of action and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
382
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 476 publications
(398 citation statements)
references
References 32 publications
13
382
1
2
Order By: Relevance
“…S1, demonstrating that dosing is sufficient and tolerated for this mouse strain. In contrast, previous work has shown that tazemetostat induces robust tumor regressions in multiple tumor models bearing EZH2 gain-of-function mutations (30).…”
Section: Effects Of Tazemetostat In Wild-type Versus Mutant Ezh2 Cellmentioning
confidence: 62%
See 2 more Smart Citations
“…S1, demonstrating that dosing is sufficient and tolerated for this mouse strain. In contrast, previous work has shown that tazemetostat induces robust tumor regressions in multiple tumor models bearing EZH2 gain-of-function mutations (30).…”
Section: Effects Of Tazemetostat In Wild-type Versus Mutant Ezh2 Cellmentioning
confidence: 62%
“…No cell line was passaged for more than 6 months prior to an experiment. Culture of diffuse large B-cell lymphoma cells WSU-DLCL2, SU-DHL-10, Toledo, and OCI-LY19 has been described previously (24,30). KARPAS-422 (ACC 32), OCI-LY7 (ACC 688), SU-DHL-5 (ACC 571), and OCI-LY3 (ACC 761) were obtained from DSMZ (German Collection of Microorganisms and Cell Cultures).…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…First molecules that directly target EZH2 and compete with the cofactor S-adenosylmethionin (SAM) binding have been described. The inhibitor E7438 has shown efficacy in SMARCB1-mutant Rhabdoid tumors (16) and as well as GSK126 and other reported EZH2 inhibitors (17,18), in EZH2-mutant non-Hodgkin lymphoma (19) where activating mutations are described (20). In addition, effects of EZH2 inhibitors in melanoma (21) (26).…”
Section: Introductionmentioning
confidence: 90%
“…Several lines of evidence suggest that EZH2 deregulation is an important driver of cancer development and progression and that inactivation of EZH2 may be therapeutically effective in many cancers [4,5,11,12,73,[76][77][78][79][80][81][82][83][84][85][86][87][88][89] . EZH2 is highly expressed in a wide range of cancer types, including lung, breast, colon, prostate, bladder and pancreatic cancer, as well as sarcomas and lymphomas [4,5,11,12,76,77,80,82,83,[85][86][87][88] .…”
Section: Prc2 and Diseasesmentioning
confidence: 99%